Race in Ralph Ellison's Invisible man [ - Haugen, Hayley Mitchell , 1968-; Gale Group (Detroit, MichiganGreenhaven Press, 2012)
Provides in-depth analysis of the life, works, career, and critical importance of author, Ralph Ellison
ch 1. Background on Ralph Ellison -- ch 2. Race in Invisible man -- ch 3. Contemporary perspectives on race
Description based on print version record
Includes bibliographical references and index
Keywords: Ellison, Ralph; Social problems in literature; United States